2016
DOI: 10.1038/nphoton.2016.248
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a self-pulsing photonic crystal Fano laser

Abstract: Semiconductor lasers in use today rely on mirrors based on the reflection at a cleaved facet or Bragg reflection from a periodic stack of layers. Here, we demonstrate an ultra-small laser with a mirror based on the Fano resonance between a continuum of waveguide modes and the discrete resonance of a nanocavity. The Fano resonance leads to unique laser characteristics. Since the Fano mirror is very narrow-band compared to conventional lasers, the laser is single-mode and in particular, it can be modulated via t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
139
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(143 citation statements)
references
References 35 publications
3
139
0
1
Order By: Relevance
“…In 1994, Dowling et al proposed a one-dimensional (1D) PC operating near the photonic band edge [2], making use of slow-light modes to increase the power emitted by such lasers, which has been one of the limitations of microcavity lasers [3]. Experimentally, slow-light band edge lasers have now been demonstrated in both two-dimensional (2D) [4][5][6][7][8][9][10][11][12] and three-dimensional (3D) [13][14][15] architectures, while over the past decade, significant progress has been made in the optimization of these lasers [15][16][17][18], allowing for the investigation of new operation regimes such as single emitter lasing [19], ultrahigh speed modulation [20], and self-pulsing [21]. To directly model the optical properties of open-system microcavity structures, finite-difference time-domain (FDTD) techniques are often employed since such open cavities support quasinormal modes (QNMs) that have a finite lifetime due their coupling to a continuum of modes with outgoing boundary conditions [22].…”
Section: Introductionmentioning
confidence: 99%
“…In 1994, Dowling et al proposed a one-dimensional (1D) PC operating near the photonic band edge [2], making use of slow-light modes to increase the power emitted by such lasers, which has been one of the limitations of microcavity lasers [3]. Experimentally, slow-light band edge lasers have now been demonstrated in both two-dimensional (2D) [4][5][6][7][8][9][10][11][12] and three-dimensional (3D) [13][14][15] architectures, while over the past decade, significant progress has been made in the optimization of these lasers [15][16][17][18], allowing for the investigation of new operation regimes such as single emitter lasing [19], ultrahigh speed modulation [20], and self-pulsing [21]. To directly model the optical properties of open-system microcavity structures, finite-difference time-domain (FDTD) techniques are often employed since such open cavities support quasinormal modes (QNMs) that have a finite lifetime due their coupling to a continuum of modes with outgoing boundary conditions [22].…”
Section: Introductionmentioning
confidence: 99%
“…Coupled‐cavity structures can also readily be realized, which has been shown to give rise to rich dynamical properties . Recently a new type of photonic crystal laser was demonstrated, where one of the laser mirrors is due to a Fano resonance between a continuum of waveguide modes and a side‐coupled nanocavity. It was shown that this so‐called Fano laser has a regime of operation, where it generates a high‐repetition‐rate train of short optical pulses, attributed to a mirror reflectivity that increases with laser intensity .…”
Section: Introductionmentioning
confidence: 99%
“…Recently a new type of photonic crystal laser was demonstrated, where one of the laser mirrors is due to a Fano resonance between a continuum of waveguide modes and a side‐coupled nanocavity. It was shown that this so‐called Fano laser has a regime of operation, where it generates a high‐repetition‐rate train of short optical pulses, attributed to a mirror reflectivity that increases with laser intensity . The realization of ultra‐compact lasers that generate short optical pulses are of interest for applications, e.g., in on‐chip optical signal processing.…”
Section: Introductionmentioning
confidence: 99%
“…We show that this interaction results in the Fano resonance, which is a typical sign of the interaction of high-quality dark and lowquality bright modes. In spite of the fact that the research of Fano resonance in photonic and plasmonic structures is a hot topic now [13][14][15][16][17][18], we do not know any investigation devoted nanoslits (Some figures may appear in colour only in the online journal)…”
Section: Introductionmentioning
confidence: 99%